Answer:
Four
Step-by-step explanation:
Let's expand and see how many nonzero terms:
⇒ (x+4)(2x²+3x+9)-3(x³-2x²+7x)=
⇒ 2x³ + 3x² + 9x + 8x² + 12 + 36 - 3x³ + 6 x² - 21 x=
⇒ - x³ + 17x² - 12x + 12
As we see the expression has four nonzero terms
So in order it goes from: 0.6, 0.02, 0.007
Since the two measures are vertical angles, you want to set them equal to each other :
6x+7=8x-17
-6x -6x
——————
7=2x-17
+17 +17
———————
24= 2x
X= 12
———
The answer is 12.
Answer: 0.5
1) convert to I proper fraction
2) divide the fraction